2017
DOI: 10.21275/art20178429
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Annealing on the Structural and Optical Properties of Mn2O3 Thin Film Prepared by Chemical Spray Pyrolysis

Abstract: Thin films of Mn 2 O 3 are synthesized using a simple chemical spray pyrolysis method on substrate from glass and then annealed in 400 o C for one hour in air. By using the X-ray diffraction wecharacterize the Structure properties of the deposited films, The results indicate that the films are polycrystalline with cubic structure with a strong (222) preferred orientation .Atomic force microscope (AFM) was used to study Morphological properties of the samples. By Using UV-VIS spectrometer the energy band gap an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 3 publications
1
3
1
Order By: Relevance
“…As a result of the process of pyrolysis of MnCl2 salt during interaction with atmospheric oxygen, a film of the binary bixbite compound α-Mn2O3 with n-type electrical conductivity and resistivity ρ ≈ 10 7 Ω•cm at room temperature is grown on the surface of the substrates. The band gap Eg ≈ 2.12 eV of the obtained films is in good agreement with the values of Eg given in the literature sources Eg  2.02 eV [12], Eg  2.2÷2.4 eV [13]. The n-Mn2O3 films grown by the spray-pyrolysis method have a high resistivity and a small electron diffusion coefficient Dn  5•10 -3 cm 2 /s [14].…”
Section: -2supporting
confidence: 89%
“…As a result of the process of pyrolysis of MnCl2 salt during interaction with atmospheric oxygen, a film of the binary bixbite compound α-Mn2O3 with n-type electrical conductivity and resistivity ρ ≈ 10 7 Ω•cm at room temperature is grown on the surface of the substrates. The band gap Eg ≈ 2.12 eV of the obtained films is in good agreement with the values of Eg given in the literature sources Eg  2.02 eV [12], Eg  2.2÷2.4 eV [13]. The n-Mn2O3 films grown by the spray-pyrolysis method have a high resistivity and a small electron diffusion coefficient Dn  5•10 -3 cm 2 /s [14].…”
Section: -2supporting
confidence: 89%
“…Band gaps of Mn 2 O 3 (oP80) were estimated to be 2.17 and 2.4 eV for nanoparticles and thin films, respectively, whereas our calculated band gap is 3.0 eV [57,58]. Based on our calculations, Mn 2 O 3 (cI80) is a metallic conductor, whereas some experimental studies of nanostructured modifications suggest that the material possesses a band gap (1.24 or 1.8 eV) [57,115]. In this case, however, it is difficult to compare the results as the experimental studies also found that the band gap of Mn 2 O 3 (cI80) is directly correlated with the size of the nanoparticles (increased size leads to a smaller band gap).…”
Section: Magnetic Binary 3d-metal Oxidescontrasting
confidence: 58%
“…A direct comparison of the electronic structure of the Mn 2 O 3 modifications with experiments is not possible due to the absence of experimental data on bulk materials. Band gaps of Mn 2 O 3 (oP80) were estimated to be 2.17 and 2.4 eV for nanoparticles and thin films, respectively, whereas our calculated band gap is 3.0 eV [57,58]. Based on our calculations, Mn 2 O 3 (cI80) is a metallic conductor, whereas some experimental studies of nanostructured modifications suggest that the material possesses a band gap (1.24 or 1.8 eV) [57,115].…”
Section: Magnetic Binary 3d-metal Oxidesmentioning
confidence: 51%
“…As a manganese oxide semiconductor, heterojunctions with g-C3N4 [7], СuOx [8], Fe2O3/Mn2O3 [9], n-Mn2O3/n-CdZnTe [10] are used. Thin films of Mn2O3 with a band gap Eg  2.01÷2.4 eV [11,12] are promising as a frontal material for heterojunctions. -Mn2O3 films are produced by spray-pyrolysis [12,13], electrodeposition [14], sol-gel method [15] etc.…”
Section: Introductionmentioning
confidence: 99%
“…Thin films of Mn2O3 with a band gap Eg  2.01÷2.4 eV [11,12] are promising as a frontal material for heterojunctions. -Mn2O3 films are produced by spray-pyrolysis [12,13], electrodeposition [14], sol-gel method [15] etc. The spray-pyrolysis method is characterized by simple hardware implementation and mobility of mode correction in the production of -Mn2O3 films with given physical properties.…”
Section: Introductionmentioning
confidence: 99%